The donkey egg - Stevens, Janet; Crummel, Susan Stevens (Houghton Mifflin Harcourt, 2019)
After fast-talking Fox leaves him with a large, green egg, Bear spends minutes, hours, days, and weeks lovingly caring for it with the help of his neighbor Hare.